Ageing in Times of the COVID-19 Pandemic - Simonson, Julia; Wünsche, Jenna; Tesch-Römer, Clemens (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2023)
This Open Access Book contains reports on the situation of people in the second half of life during the first year of the Covid-19 pandemic. The analyses are based on the German Ageing Survey (DEAS) and they provide insights on four main areas of life: income and work, subjective health and well-being, social support and loneliness as well as societal participation. This book is useful for scientists as well as political actors by directing attention to the risk groups that have been hard hit by the pandemic while also highlighting the resilience and adaptive capacities of many people in the second half of life. The Editors Dr. Julia Simonson, Dr. Jenna Wünsche and Prof. Dr. Clemens Tesch-Römer work at the German Centre of Gerontology (DZA).